The global development of value orientations, political support and democracy since the 1990s - Hoffmann-Lange, Ursula (Frontiers in Political Science, 2024)
This article analyzes the global development of democracy since the 1990s. The theoretical introduction is followed by a descriptive analysis of several indices of political support based on survey results for 89 countries that participated at least twice in the World Values Survey (WVS) or the European Values Study (EVS). The analysis focuses on emancipative value orientations measured by Welzel's Choice Index and several indicators of political support. The scores of these indicators are broken down by five regime types and seven world regions. The results confirm that the global decline of democratic quality since the mid-2000s has not been as dramatic as the pessimistic analyses of Freedom House and the V-Dem project have claimed. It has primarily taken place in a limited number of populous countries on which these publications have focused. When countries are treated equally, the quality of democracy has remained remarkably stable since the early 1990s. Emancipative values are globally on the rise, but their increase has been considerably higher in the established democracies. This supports the skeptical argument that they cannot be considered as the major cause of the third wave of democratization. The descriptive analysis is complemented by regression analyses for confidence in regime institutions and support for democracy as dependent variables. The evaluation of democratic regime performance is the strongest predictor of confidence in regime institutions. An intrinsic conception of democracy and the importance assigned to living in a democracy have the strongest influence on support for democracy. Emancipative value orientations have a minor influence on political support even in consolidated democracies. Finally, the analysis does not confirm the suspected relationship between the different levels of political support. Easton's theory of political support assumed that they mutually influence each other via a generalization of experiences or an overflow of values. Instead, it seems that confidence in regime institutions and support for democracy follow different cognitive logics.